2018
DOI: 10.3389/fphys.2018.00205
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Action Potential Restitution Contributes to Mechanical Restitution in Right Ventricular Myocytes From Pulmonary Hypertensive Rats

Abstract: We investigated the steepened dynamic action potential duration (APD) restitution of rats with pulmonary artery hypertension (PAH) and right ventricular (RV) failure and tested whether the observed APD restitution properties were responsible for negative mechanical restitution in these myocytes. PAH and RV failure were provoked in male Wistar rats by a single injection of monocrotaline (MCT) and compared with saline-injected animals (CON). Action potentials were recorded from isolated RV myocytes at stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…8 ) and NCX current (Fig. S4) and have recently reported that membrane stability is decreased in these cells [ 22 ]. Thus, the decrease in WCEs in response to BB can be explained by the decrease in SR Ca 2+ load and intermediate level of Kir2.1 expression in MCT + BB myocytes.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…8 ) and NCX current (Fig. S4) and have recently reported that membrane stability is decreased in these cells [ 22 ]. Thus, the decrease in WCEs in response to BB can be explained by the decrease in SR Ca 2+ load and intermediate level of Kir2.1 expression in MCT + BB myocytes.…”
Section: Discussionmentioning
confidence: 85%
“…In addition we have previously shown that the contraction-frequency relationship in MCT myocytes is influenced by BB via expression of creatine kinase [ 15 , 16 ]. Repolarization profile can modulate Ca 2+ handling [ 5 ] and we have shown that in MCT myocytes the stimulation frequency dependent fall in contraction is, at least in part, caused by the stimulation frequency dependent fall in action potential duration (APD) [ 3 , 22 ]. Therefore, the prolonged APD and QT interval occurring in the MCT model may facilitate greater SR load through enhanced Ca 2+ entry, while steeper APD restitution contributes to the steeper stimulation frequency dependent fall in Ca 2+ transient amplitude [ 3 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…2528 Some prominent studies indicate the presence of a proarrhythmic substrate in hearts of MCT-treated rats, and among the causes of sudden death are the changes in Ca 2+ and K + channel activity and electrical restitution. 2932…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Some prominent studies indicate the presence of a proarrhythmic substrate in hearts of MCT-treated rats, and among the causes of sudden death are the changes in Ca 2þ and K þ channel activity and electrical restitution. [29][30][31][32] Pulmonary arterial stiffness increases in late PAH Pulmonary arterial stiffening markedly increased and became significantly different from the control group to the MCT-injected rats after three weeks. Pulmonary arterial elastance E a values increased as PAH advanced, which has also been reported by other groups when using the rat MCT model: Yin et al from 0.5 AE 0.14 to 0.79 AE 0.3 mmHg/mL; 18 and de Man et al from 0.15 to 1.0 mmHg/mL.…”
Section: Mct-model Of Pah Shows Features Of Preserved Cardiac Functionmentioning
confidence: 96%
“…In contrast to mice, recordings in rat preparations typically do not demonstrate shortening of APD 90 at fast pacing rates ( Benoist et al, 2011 , 2012 ). However, APD restitution has been observed in a rat model of pulmonary hypertension and was recently implicated in the induction of negative mechanical restitution in this model ( Hardy et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%